Analisis Dampak Perilaku Online Gen Z Terhadap Identitas Kewarganegaan Dalam Era Digital - Melsya Dwi Putri; Emilia Susanti; Lara Santri; Nopalia Susanti; Rasti Ananda; Daimatussalimah Daimatussalimah (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This research analyzes the impact of generation Z's online behavior on civic identity in the digital era. By utilizing qualitative methodology, this study examines how interactions on social media, consumption of digital information, and participation in virtual communities influence Gen Z's civic views and attitudes. The results show that online behavior can strengthen political awareness, facilitate engagement in social issues, and influencing civic identity through the formation of public opinion and social mobilization. However, this research also reveals challenges such as the spread of disinformation and social fragmentation that can obscure broader understandings of citizenship. In conclusion, although Gen Z's online behavior has the potential to enrich civic identity, strong digital literacy and supporting policies are needed so that its positive impact can be optimized.